Lighting System With Hybird Energy Supply For Energy Efficiency and Security Feature of the Building - Renny Rakhmawati; Safira Nur Hanifah (IC-ITECHS, 2014)
Recently, many buildings’ outside corridors have less lighting system at night, because their lamps mostly depend upon electrical energy from PLN (State Electrical Company). It affects the whole electrical power used. Due to this condition, we need to arrange the lamps’ light to reduce electrical power. This research is going to create an automatic lighting efficiency system which is located outside of the building’s corridor; and it uses time setting with the application of RTC (Real Time Clock) to detect human motion with motion-sensor detector (PIR). The primary aim of this research is to manage electrical energy more efficiently and to make a safety measure for the building itself. When PIR sensor detects any motion in safety-time-range that has been set before, it will send a short message to the central security system. It is supplied by hybrid system between solar cell and PLN electrical power. Though the use of the solar cell, an output voltage of 17-19 volt will be reduced through the buck converter to stabilize enough while filling 12-volt the accumulator. The output electrical voltage derived from accumulator will be converted from 12 Vdc to 12 Vac by an inverter; and then it will be increased to 220 Vac by step up voltage regulator to supply its lighting load. Otherwise, if the accumulator is not able to fulfill the supply, a microcontroller will force swith circuit to gain the lighting load another supply from PLN electrical power source. By implementing this management system, total energy within 10 hours (17.00-03.00 WIB) is 420 Wh; and it reduces the energy for 105 Wh with 25% efficiency.